FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PERDA NO 10 TAHUN 2012 TENTANG RETRIBUSI PELAYANAN PERSAMPAHAN /KEBERSIHAN DI KECAMATAN MARPOYAN DAMAI - Iriani, Ovi; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Levies are local taxes as payment for services or granting special permits provided and granted by the regional government for the benefit of individuals or bodies. A phenomenon that can be seen in the field, namely: 1. The collection of the levy exceeds a predetermined from tariff of local regulations No. 10 of 2012 concerning levy waste services / cleanliness. 2. Facilities and infrastructure is inadequate due to a lack of fleets. 3. Less irregular schedule due to lack of transport of the fleet. This study aims to find out what are the factors that affect the implementation of Regulation No. 10 Year 2012 on Service Fees Waste / Hygiene in Marpoyan Damai District in 2014.This research uses descriptive analysis with a qualitative approach. The data source consists of primary data is data that is obtained from the Marpoyan Damai District. While secondary data is data sourced from the Marpoyan District documentation of Peace as well as revenue. The collection of data through observation, interviews and documentation. Analysis techniques of data is presentation of data analysis techniques, and drawing conclusions and testing.The results showed that the order to determine the factors that inhibit the levy garbage / hygiene in the Marpoyan Damai district includes variables as follows: (1) The communication is meant process of delivering the policy objectives of retribution garbage from the District Marpoyan Peace by means of socialization to the community topdown. (2) Resources are defined in this study is for the overall financial and nonfinancial factors needed to carry out the organizational activities of the activities in the program districts fare collection and transportation of garbage. (3) Disposition referred to in this research is the attitude of the district head has shown firmness to the janitor in fare collection and transportation of garbage. (4) The structure of the bureaucratic point is the composition and the relationship between the unit and its functions and operational procedures within institutions related agencies working unit.Keywords: public policy, policy implementation, public service